Patient Characteristics and Clinical and Intraoperative Variables Affecting Outcome in Pediatric Traumatic Brain Injury - Dhanda, Ankur; Bindra, Ashish; Dhakal, Roshni; Chavali, Siddharth; Singh, Gyaninder P.; Singh, Pankaj K.; Mathur, Purva (Journal of Neuroanaesthesiology and Critical Care, 2021)
Background Pediatric traumatic brain injury (TBI) has distinctive pathophysiology and characteristics that differ from adults. These can be attributed to age-related anatomical and physiological differences and distinct patterns of injuries seen in children. Our aim was to identify the patient characteristics, clinical variables during intensive care and intraoperative management associated with poor functional outcome in a cohort of pediatric TBI patients.Methods Retrospective chart review of pediatric TBI patients admitted to neurotrauma intensive care unit (NICU) over a period of 1 year.Results A total of 105 children (< 12 years) with head injury were admitted in the NICU during the study period. The most common mechanism of injury was fall in 78% cases. Fifty-four patients (51.4%) presented with a severe head injury (Glasgow coma scale [GCS] ≤ 8), while 31 (29.5%) and 20 (19.1%) had a mild and moderate head injury. The most common finding was skull fractures (59%), contusions (36.2%), and subdural hematoma (SDH) (30.4%). Forty nine patients (46.7%) required surgical management. The median duration of anesthesia was 205 (interquartile range [IQR] 65, 375) minutes, and median blood loss during the surgery was 16.7 mL/kg body weight with 41% requiring intraoperative blood transfusions. Median duration of ICU and hospital stay was 5 (IQR 1, 47) and 8 (IQR 1, 123) days, respectively. GOS at discharge ≤ 3 representing poor outcome was present in 35 patients (33.3%). Mortality was seen in 15 (14.3%) patients. Multivariate analysis identified postresuscitation GCS ≤ 8 on admission as independent predictor of mortality, and postresuscitation GCS ≤ 8 on admission and NICU stay of > 7 days as independent predictor of poor outcome.Conclusion Despite advances in neurointensive care, mortality and morbidity remains high in pediatric head trauma and is mainly dependent on postresuscitation GCS and NICU stay of more than 7 days. Multidimensional approach is required for its prevention and management.
Keywords: Glasgow outcome score; intensive care unit; pediatric; traumatic brain injury